A socio-environmental vulnerability map to evaluate the sustainability of small hydroelectric power stations in Southeastern Brazil - Mello, Roxane Lopes de; Simoes, Silvio Jorge C. [UNESP] (Inderscience Enterprises Ltd, 2020)
It is understood that hydroelectricity generation through small hydropower stations is a sustainable alternative. However, in order to assess their sustainability, it is necessary to evaluate the socio-environmental vulnerability of a given region. This paper aims to analyse the socioenvironmental vulnerability from the impact of a small hydropower plant in Sao Luiz do Paraitinga, a municipality which is 180 km away from Sao Paulo city, Brazil. The methodology is based on principles of the analytical hierarchy process (AHP) in order to produce the Socio-Environmental Vulnerability Index (SEVI) Map. The results indicate that there is significant overlap between areas that are susceptible to physical processes of environmental vulnerability and those that present the worst social indicators. The results herein indicate a starting point for a more in-depth analysis of the socioenvironmental vulnerability of areas under the influence of small hydropower plants, which requires planning and mitigating actions to address such vulnerability.
Keywords: small hydroelectricity stations; GIS; geographical information system; AHP; analytical hierarchy process; social-environmental sustainability